Solid electrolyte precursor, solid electrolyte and preparation method thereof, and battery

By adopting a solid electrolyte precursor with a core-shell structure in a solid-state battery, the uniform coating layer is used to improve the distribution uniformity of lithium elements, the problem of uneven distribution of lithium sources in the prior art is solved, and higher ionic conductivity and battery performance are achieved.

CN119751058APending Publication Date: 2025-04-04SHENZHEN INX ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510249609.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the preparation of existing solid-state batteries, the uniformity and ionic conductivity of the oxide solid electrolyte are affected by the problem of uneven distribution of lithium sources, which affects the performance of the battery.

Method used

A solid electrolyte precursor with a core-shell structure is used to dissolve the lithium supplement agent in a solvent and mix it with the oxide solid electrolyte to form a uniform cladding layer to ensure the uniform distribution of lithium elements.

Benefits of technology

Through uniform lithium element distribution, the ionic conductivity and uniformity of the solid electrolyte are improved, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751058A_ABST
    Figure CN119751058A_ABST
Patent Text Reader

Abstract

The present application relates to a solid electrolyte precursor, a solid electrolyte, a preparation method thereof, and a battery to improve the ionic conductivity of the solid electrolyte and reduce the defects caused by uneven lithium sources during the sintering process. The preparation method of the solid electrolyte precursor includes: adding a lithium supplement and an oxide solid electrolyte to a solvent for mixing to obtain a first mixture, wherein the lithium supplement is dissolved in the solvent; drying the first mixture, removing the solvent so that the lithium supplement is precipitated and formed into a coating layer on the surface of the oxide solid electrolyte, to obtain a solid electrolyte precursor with a core-shell structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte precursor, a solid electrolyte and a preparation method thereof, and a battery. Background Art

[0002] In the existing solid-state battery preparation process, the performance of oxide solid electrolytes depends largely on the density and uniformity of the oxide solid electrolytes. In order to obtain high-performance oxide solid electrolytes, it is usually necessary to supplement the oxide solid electrolyte powder with lithium before sintering.

[0003] The traditional lithium replenishment method is to directly dry-mix oxide solid electrolyte powder with a lithium source (such as LiOH, Li2CO3, etc.). However, this method can easily lead to uneven distribution of the lithium source, affecting the uniformity of the oxide solid electrolyte obtained after sintering, and further affecting the ionic conductivity of the oxide solid electrolyte. Summary of the invention

[0004] The embodiments of the present application provide a solid electrolyte precursor, a solid electrolyte and a preparation method thereof, and a battery to solve the technical problem of improving the ionic conductivity of the solid electrolyte.

[0005] In a first aspect, an embodiment of the present application provides a solid electrolyte precursor, wherein the solid electrolyte precursor is a core-shell structure, including a core composed of an oxide solid electrolyte and a shell composed of a lithium supplement. In one embodiment, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:(0.5~5).

[0006] In one embodiment, the lithium supplement includes at least one of lithium hydroxide, lithium carbonate and lithium oxide.

[0007] In one embodiment, the oxide solid electrolyte is in the form of spherical or quasi-spherical particles.

[0008] In one embodiment, the average particle size of the oxide solid electrolyte is 5 nm to 1 μm.

[0009] In a second aspect, an embodiment of the present application provides a method for preparing a solid electrolyte precursor, comprising: Adding a lithium supplement agent and an oxide solid electrolyte into a solvent for mixing to obtain a first mixture, wherein the lithium supplement agent is dissolved in the solvent; The first mixture is dried to remove the solvent so that the lithium supplement agent is precipitated and forms a coating layer covering the surface of the oxide solid electrolyte, thereby obtaining a solid electrolyte precursor having a core-shell structure.

[0010] In one embodiment, the lithium supplement comprises an inorganic lithium compound, and the solvent comprises water.

[0011] In one embodiment, the inorganic lithium compound includes at least one of lithium hydroxide, lithium carbonate and lithium oxide.

[0012] In one embodiment, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum zirconium gallium oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium aluminum titanium phosphate.

[0013] In one embodiment, in the first mixture, the molar ratio of the lithium element in the oxide solid electrolyte to the lithium element in the lithium supplement is 10:(0.5-5).

[0014] In one embodiment, in the first mixture, the average particle size of the oxide solid electrolyte is 5 nm to 1 μm.

[0015] In one embodiment, the method for preparing the solid electrolyte precursor further comprises: before preparing the first mixture, performing a sand grinding treatment on the oxide solid electrolyte so that the oxide solid electrolyte is in the form of spherical or quasi-spherical particles.

[0016] In one embodiment, the method for preparing the solid electrolyte precursor further comprises: before drying the first mixture, ball milling the first mixture.

[0017] In one embodiment, the preparation process of the first mixture comprises: Adding a lithium supplement agent into a solvent for dissolution to obtain a first solution; An oxide solid electrolyte is added into the first solution and stirred to obtain a first mixture.

[0018] In a third aspect, an embodiment of the present application provides a solid electrolyte, which is obtained by sintering the solid electrolyte precursor as described above or the solid electrolyte precursor prepared by the preparation method of the solid electrolyte precursor as described above.

[0019] In a fourth aspect, an embodiment of the present application provides a method for preparing a solid electrolyte, comprising: Providing a solid electrolyte precursor, wherein the solid electrolyte precursor is the solid electrolyte precursor as described above or a solid electrolyte precursor prepared by the method for preparing the solid electrolyte precursor as described above; The solid electrolyte precursor is sintered to obtain a solid electrolyte.

[0020] In one embodiment, the solid electrolyte is a solid electrolyte membrane, and the sintering treatment of the solid electrolyte precursor to obtain the solid electrolyte comprises: mixing the solid electrolyte precursor with a binder to obtain a second mixture; Roll-pressing the second mixture to obtain a solid electrolyte green film; The solid electrolyte green film is sintered to obtain a solid electrolyte membrane.

[0021] In one embodiment, the sintering temperature of the sintering treatment is 1000° C. to 1300° C., and the sintering time is 5 min to 10 h.

[0022] In a fifth aspect, an embodiment of the present application provides a battery, comprising a solid electrolyte as described above or a solid electrolyte prepared by the method for preparing a solid electrolyte precursor as described above.

[0023] Beneficial effects of the embodiments of the present application: In an embodiment of the present application, the preparation method of the solid electrolyte precursor provided is by dissolving the lithium supplement agent in a solvent and mixing it with an oxide solid electrolyte, so that the lithium supplement agent is uniformly covered on the surface of the oxide solid electrolyte under the action of the solvent, and further combined with a drying process, so that the solvent is volatilized, and the lithium supplement agent is gradually precipitated and formed into a continuous coating layer coated on the surface of the oxide solid electrolyte to obtain a solid electrolyte precursor. The solid electrolyte precursor has a core-shell structure, wherein the core is an oxide solid electrolyte and the shell is a lithium supplement agent. During the sintering process, the lithium supplement agent in the coating layer (ie, the shell) can be used as a lithium source to uniformly compensate for the lithium volatilized by the oxide solid electrolyte during the sintering process, thereby ensuring the uniformity of the obtained oxide solid electrolyte, and then improving the ionic conductivity of the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0025] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings, wherein the same figure numbers represent the same parts in the following description.

[0026] Figure 1 is a schematic structural diagram of a solid electrolyte precursor provided in an embodiment of the present application; Figure 2 This is a scanning electron microscope image of the oxide solid electrolyte LLZO powder coated with the lithium supplement LiOH provided in Example 1 of the present application; Figure 3 This is a scanning electron microscope image of a conventional lithium-supplemented electrolyte powder provided in Comparative Example 1 of the present application; Figure 4 is a scanning electron microscope image of the ceramic electrolyte membrane provided in Example 1 of the present application; Figure 5 This is a scanning electron microscope image of the ceramic electrolyte membrane provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0028] First, see Figure 1 The embodiment of the present application provides a solid electrolyte precursor, which is a core-shell structure, including a core 1 composed of an oxide solid electrolyte and a shell 2 composed of a lithium supplement. The solid electrolyte precursor can be sintered to obtain a solid electrolyte. The solid electrolyte precursor is a core-shell structure, that is, the solid electrolyte precursor includes a core 1 and a shell 2, and the shell 2 is a coating layer coated on the surface of the core 1. The core 1 contains an oxide solid electrolyte, and the shell 2 contains a lithium supplement.

[0029] Oxide solid electrolyte is a compound composed of lithium, oxygen and other elements (such as phosphorus, titanium, aluminum, etc.). Oxide electrolyte has the advantages of high ionic conductivity, high mechanical strength, good thermal stability and wide electrochemical window. The use of oxide electrolyte to prepare solid electrolyte is conducive to improving the performance of solid electrolyte.

[0030] Optionally, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium aluminum oxide (LLAZO), lithium lanthanum zirconium gallium oxide (LLGZO), lithium lanthanum titanium oxide (LLTO), lithium aluminum germanium phosphate (LAGP) and lithium aluminum titanium phosphate (LATP).

[0031] Lithium replenisher refers to a substance that can provide lithium. Since the solid electrolyte precursor needs to be sintered before the solid electrolyte is prepared, and the temperature is high during the sintering process, the lithium in the lattice of the oxide solid electrolyte is easily volatilized, resulting in a crystal phase transformation, generating a second phase without lithium ions, and reducing the ionic conductivity of the prepared solid electrolyte. The addition of lithium replenisher can compensate for the volatilized lithium during the sintering process, reduce the risk of crystal phase transformation, and thus improve the ionic conductivity of the prepared solid electrolyte. In other words, the lithium replenisher is used to replenish the lithium volatilized from the oxide solid electrolyte during the sintering process.

[0032] The solid electrolyte precursor provided in the embodiment of the present application is obtained by coating a lithium supplement agent as a shell on the surface of a core comprising an oxide solid electrolyte. The lithium supplement agent can serve as a lithium source to uniformly compensate for the lithium volatilized from the oxide solid electrolyte during sintering, thereby ensuring the uniformity of the obtained oxide solid electrolyte and further improving the ionic conductivity of the solid electrolyte.

[0033] In some embodiments, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:(0.5~5). By controlling the ratio of the lithium in the oxide solid electrolyte to the lithium in the lithium supplement to be 10:(0.5~5), the lithium supplement can not only effectively compensate for the lithium volatilized during the sintering process of the oxide solid electrolyte, but also allow a small amount of lithium to remain at the grain boundary to form a lithium-rich phase, thereby better connecting the oxide solid electrolyte grains and improving the compactness of the solid electrolyte obtained after sintering. As an example, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:0.5, 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:4, 10:4.5 or 10:5.

[0034] In some embodiments, the lithium supplement includes at least one of lithium hydroxide (LiOH), lithium carbonate (Li2CO3) and lithium oxide.

[0035] In some embodiments, the oxide solid electrolyte is a spherical or quasi-spherical particle. The oxide solid electrolyte is configured as a spherical or quasi-spherical particle, so that the lithium supplementer can coat the oxide solid electrolyte more uniformly.

[0036] In some embodiments, the average particle size of the oxide solid electrolyte is 5nm~1μm. If the average particle size of the oxide solid electrolyte is too large or too small, the lithium replenishing effect of the lithium replenishing agent on the oxide solid electrolyte will be reduced. Generally, the larger the average particle size of the oxide solid electrolyte, the longer the path of the lithium replenishing agent coated on the surface of the oxide solid electrolyte to enter the interior of the oxide solid electrolyte, and the difficulty of obtaining supplementary lithium ions inside the oxide solid electrolyte increases, resulting in uneven lithium replenishment; the smaller the average particle size of the oxide solid electrolyte, the greater the probability and difficulty of obtaining lithium replenishment by the lithium replenishing agent in the lattice where lithium volatilization occurs inside the oxide solid electrolyte, but if the average particle size of the oxide solid electrolyte is too small, the oxide solid electrolyte is prone to agglomeration, which in turn affects the coating effect of the lithium replenishing agent on the oxide solid electrolyte, and instead leads to uneven lithium replenishment. In addition, the larger the average particle size of the oxide solid electrolyte, the longer the time required for the sintering process will be, resulting in increased production costs. As an example, the average particle size of the oxide solid electrolyte is 5 nm, 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1 μm.

[0037] In a second aspect, an embodiment of the present application provides a method for preparing a solid electrolyte precursor, comprising: S11, adding a lithium supplement agent and an oxide solid electrolyte into a solvent for mixing to obtain a first mixture, wherein the lithium supplement agent is dissolved in the solvent; S12, drying the first mixture to remove the solvent so that the lithium supplement agent is precipitated and forms a coating layer on the surface of the oxide solid electrolyte to obtain a solid electrolyte precursor with a core-shell structure.

[0038] Oxide solid electrolyte is a compound composed of lithium, oxygen and other elements (such as phosphorus, titanium, aluminum, etc.). Oxide electrolyte has the advantages of high ionic conductivity, high mechanical strength, good thermal stability and wide electrochemical window. The use of oxide electrolyte to prepare solid electrolyte is conducive to improving the performance of solid electrolyte.

[0039] In some embodiments, the oxide solid electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium aluminum oxide (LLAZO), lithium lanthanum zirconium gallium oxide (LLGZO), lithium lanthanum titanium oxide (LLTO), lithium aluminum germanium phosphate (LAGP), and lithium aluminum titanium phosphate (LATP).

[0040] As an example, the chemical formula of lithium lanthanum zirconium oxide (LLZO) is Li7La3Zr2O 12 .

[0041] As an example, the chemical formula of lithium lanthanum zirconium tantalum oxide (LLZTO) is Li7-x Ln3Z 2-x Ta x O 12 , for example, when x=0.5, the chemical formula is Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 .

[0042] As an example, the chemical formula of lithium lanthanum zirconium aluminum oxide (LLAZO) is Li 7-3x La3Al x Zr2O 12 , for example, when x=0.2, the chemical formula is Li 6.4 La3Al 0.2 Zr2O 12 .

[0043] As an example, the chemical formula of lithium lanthanum zirconium gallium oxide (LLGZO) is Li 7-3x LqCy x Zr2O 12 , for example, when x=0.3, the chemical formula is Li 6.1 LqCy 0.3 Zr2O 12 .

[0044] As an example, the chemical formula of lithium lanthanum titanate (LLTO) is Li 2-3x La x TiO3, for example, when x=0.5, the chemical formula is Li 0.5 La 0.5 TiO3.

[0045] As an example, the chemical formula of lithium aluminum germanium phosphate (LAGP) is Li 1.5 Al 0.5 Ge 1.5 (PO4)3.

[0046] As an example, the chemical formula of lithium aluminum titanium phosphate (LATP) is Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0047] A lithium supplement refers to a substance that can provide lithium. Since sintering treatment is required before the solid electrolyte is prepared, and since the temperature is high during the sintering treatment, the lithium in the lattice of the oxide solid electrolyte is easily volatilized, causing the crystal phase to change, generating a second phase that does not contain lithium ions, and reducing the ionic conductivity of the prepared solid electrolyte. The addition of a lithium supplement can compensate for the volatilized lithium during the sintering treatment, reduce the risk of crystal phase change, and thus improve the ionic conductivity of the prepared solid electrolyte. In other words, the lithium supplement is used to supplement the lithium volatilized from the oxide solid electrolyte during the sintering treatment.

[0048] In some embodiments, the lithium supplement includes at least one of a lithium salt and a lithium oxide. As an example, the lithium supplement includes at least one of Li2SO4, Li2CO3, CH3COOLi, LiNO3, Li3PO4, LiHSO4, Li2O, Li2O2, LiClO4, Li2TiO3, Li2AlO3, Li2ZrO3, lithium bis(oxalatoborate), bis(difluorosulfonyl)imide, lithium difluorophosphate, and lithium 4,6-dichloropyridazine-3-carboxylate.

[0049] The lithium supplement agent is dissolved in the solvent, that is, the lithium supplement agent can be evenly dispersed in the solvent to form a homogeneous phase. As an example, the lithium supplement agent and the solvent can be selected based on similar dissolution. For example, when the lithium supplement agent is an organic lithium salt, an organic solvent can be selected to dissolve the lithium supplement agent; when the lithium supplement agent is an inorganic lithium salt, an inorganic solvent can be selected to dissolve the lithium supplement agent. Generally, oxide solid electrolytes are not easily dissolved in solvents. Since the solvent is a liquid and the liquid has fluidity, by dissolving the lithium supplement agent in the solvent, the solvent can carry the lithium supplement agent and cover the surface of the oxide solid electrolyte, thereby improving the uniformity of the mixing of the lithium supplement agent and the oxide solid electrolyte, thereby improving the ionic conductivity of the obtained solid electrolyte and reducing the defects caused by uneven lithium sources during the sintering process.

[0050] In some embodiments, the lithium supplement includes an inorganic lithium compound, and the solvent includes water. The inorganic lithium compound can be dissolved in water to obtain a lithium ion solution, and the water can be volatilized and leave the oxide solid electrolyte in the subsequent drying and sintering processes, which can reduce the risk of the solvent being converted into impurities and improve the performance of the oxide solid electrolyte. Optionally, the inorganic lithium compound includes at least one of lithium hydroxide (LiOH), lithium carbonate (Li2CO3) and lithium oxide. As an example, the lithium oxide includes at least one of Li2O and Li2O2.

[0051] In some embodiments, in the first mixture, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:(0.5~5). By controlling the ratio of the lithium in the oxide solid electrolyte to the lithium in the lithium supplement to be 10:(0.5~5), the lithium supplement can form a continuous lithium supplement layer coated on the surface of the oxide solid electrolyte after drying, so that the lithium supplement can not only effectively compensate for the lithium volatilized during the sintering of the oxide solid electrolyte, but also allow a small amount of lithium to remain at the grain boundary to form a lithium-rich phase, thereby better connecting the oxide solid electrolyte grains and improving the compactness of the solid electrolyte obtained after sintering. As an example, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:0.5, 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:4, 10:4.5 or 10:5.

[0052] In some embodiments, in the first mixture, the average particle size of the oxide solid electrolyte is 5nm~1μm. If the average particle size of the oxide solid electrolyte is too large or too small, the lithium replenishing effect of the lithium replenishing agent on the oxide solid electrolyte will be reduced. Generally, the larger the average particle size of the oxide solid electrolyte, the longer the path of the lithium replenishing agent coated on the surface of the oxide solid electrolyte to enter the interior of the oxide solid electrolyte, and the difficulty of obtaining supplementary lithium ions inside the oxide solid electrolyte increases, resulting in uneven lithium replenishment; the smaller the average particle size of the oxide solid electrolyte, the greater the probability and difficulty of obtaining lithium replenishment by the lithium replenishing agent in the lattice where lithium volatilization occurs inside the oxide solid electrolyte, but if the average particle size of the oxide solid electrolyte is too small, the oxide solid electrolyte is prone to agglomeration, which in turn affects the coating effect of the lithium replenishing agent on the oxide solid electrolyte, and instead leads to uneven lithium replenishment. In addition, if the average particle size of the oxide solid electrolyte is too large, the coating layer on the surface of the oxide solid electrolyte in the solid electrolyte precursor is also more likely to fall off, causing uneven lithium replenishment. In addition, the larger the average particle size of the oxide solid electrolyte, the longer the time required for the sintering process, resulting in increased production costs. As an example, the average particle size of the oxide solid electrolyte is 5 nm, 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1 μm.

[0053] In some embodiments, the method for preparing a solid electrolyte precursor further includes: before preparing the first mixture, sand grinding the oxide solid electrolyte, the sand grinding mainly shapes the oxide solid electrolyte so that the oxide solid electrolyte is spherical or quasi-spherical particles. Experiments have found that when the oxide solid electrolyte is shaped into spherical or quasi-spherical particles, the lithium supplement coating of the oxide solid electrolyte is more uniform, and the coating layer is not easy to fall off during subsequent processing. In addition, the sand grinding process can also make the particle size distribution of the oxide solid electrolyte more uniform, further improving the uniformity of lithium supplementation. Optionally, during the sand grinding process, the sand grinding speed is 500rpm~4000rpm, and the sand grinding time is 30min~300min. As an example, the sanding rotation speed is 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm or 4000 rpm; the sanding time is 30 min, 50 min, 100 min, 150 min, 200 min, 250 min or 300 min.

[0054] In some embodiments, step S11 (i.e., the preparation process of the first mixture) includes: S111, adding a lithium supplement agent into a solvent for dissolution treatment to obtain a first solution; S112, adding the oxide solid electrolyte to the first solution, stirring the solution, and obtaining a first mixture.

[0055] That is to say, by adding the lithium supplement and the oxide solid electrolyte into the solvent step by step, the lithium supplement is first fully dissolved in the solvent and then the oxide solid electrolyte is added. This method can ensure that the lithium supplement is fully dispersed in the oxide solid electrolyte while appropriately reducing the amount of solvent, thereby reducing the difficulty of subsequent drying treatment.

[0056] Of course, in some embodiments, the lithium supplement and the oxide solid electrolyte can also be added to the solvent together. This method is more suitable for use when the amount of solvent is relatively large, which can further improve the uniformity of the dispersion of the lithium supplement in the oxide solid electrolyte. Optionally, in the first mixture, the oxide solid electrolyte is completely immersed in the solvent. As an example, the first mixture is a suspension, and the oxide solid electrolyte is dispersed in the solvent in the form of particles.

[0057] In some embodiments, the method for preparing the solid electrolyte precursor further includes: before drying the first mixture, ball milling the first mixture. Ball milling the first mixture is mainly to further mix the oxide solid electrolyte and the lithium replenisher in the first mixture, promote the solvent to drive the lithium replenisher to cover the surface of the oxide solid electrolyte, and improve the uniformity of lithium replenishment.

[0058] In some embodiments, the ball milling speed is 400 rpm to 800 rpm, for example 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm; the ball milling time is 10 h to 20 h, for example 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.

[0059] It can be understood that after the first mixture is ball-milled, the mixing effect of the oxide solid electrolyte and the lithium supplement is improved, but there will not be much change in the chemical composition.

[0060] The purpose of drying the first mixture is to remove or substantially remove the solvent in the first mixture covering the surface of the oxide solid electrolyte, and obtain a solid electrolyte precursor, that is, the solid electrolyte precursor mainly includes an oxide solid electrolyte and a lithium supplement. Since the solvent and the lithium supplement were originally covered on the surface of the oxide solid electrolyte together, after the solvent evaporates, the lithium supplement will precipitate and be fixedly attached to the surface of the oxide solid electrolyte. Since the lithium supplement was originally dissolved in the solvent, the lithium supplement will gradually precipitate and form a continuous lithium supplement layer when the solvent evaporates, and the lithium supplement layer is coated on the surface of the oxide solid electrolyte as a coating layer. The formation of the coating layer can greatly improve the uniformity of lithium supplementation during the sintering process. It can be understood that the obtained solid electrolyte precursor is a core-shell structure, in which the core is an oxide solid electrolyte, and the coating layer is formed as a shell, that is, the shell contains a lithium supplement.

[0061] In some embodiments, drying the first mixture includes heating the first mixture to volatilize the solvent in the first mixture. Usually, the temperature during the drying process is much lower than the temperature during the sintering process to prevent damage to the structure of the oxide solid electrolyte. As an example, the solvent is water, and when the first mixture is dried, the drying temperature is 60°C to 100°C, such as 60°C, 70°C, 80°C, 90°C or 100°C.

[0062] In some embodiments, the method for preparing the solid electrolyte precursor is used to prepare the solid electrolyte precursor provided in the first aspect of the embodiment of the present application.

[0063] The preparation method of the solid electrolyte precursor provided in the embodiment of the present application comprises the steps of dissolving a lithium supplement agent in a solvent and mixing the mixture with an oxide solid electrolyte, so that the lithium supplement agent is evenly covered on the surface of the oxide solid electrolyte under the action of the solvent, and further combined with a drying treatment, so that the solvent evaporates, and the lithium supplement agent gradually precipitates and forms a continuous coating layer on the surface of the oxide solid electrolyte. During the sintering treatment, the lithium supplement agent in the coating layer can be used as a lithium source to evenly compensate for the lithium volatilized from the oxide solid electrolyte during the sintering treatment, thereby ensuring the uniformity of the obtained oxide solid electrolyte, and further improving the ionic conductivity of the solid electrolyte.

[0064] In a third aspect, an embodiment of the present application provides a solid electrolyte, which is obtained by sintering a solid electrolyte precursor prepared by the solid electrolyte precursor provided in the first aspect of the embodiment of the present application or the solid electrolyte precursor prepared by the preparation method provided in the second aspect.

[0065] Since the solid electrolyte precursor includes an oxide solid electrolyte and a lithium replenisher coated on the surface of the oxide solid electrolyte, during the sintering process, the lithium replenisher can serve as a lithium source to uniformly compensate for the lithium volatilized from the oxide solid electrolyte during the sintering process, thereby ensuring the uniformity of the obtained oxide solid electrolyte and further improving the ionic conductivity of the solid electrolyte.

[0066] In a fourth aspect, an embodiment of the present application provides a method for preparing a solid electrolyte, comprising: S21. Provide a solid electrolyte precursor, wherein the solid electrolyte precursor is a solid electrolyte precursor provided in the first aspect of the embodiment of the present application or a solid electrolyte precursor prepared by the preparation method of the solid electrolyte precursor provided in the second aspect; S22, sintering the solid electrolyte precursor to obtain a solid electrolyte.

[0067] The purpose of sintering the solid electrolyte precursor is to use the high temperature of the sintering process to rearrange and combine the interfaces between the granular oxide solid electrolytes, thereby forming a dense electrolyte structure, improving the density and ionic conductivity of the solid electrolyte, and reducing the grain boundary impedance.

[0068] In some embodiments, the solid electrolyte is a solid electrolyte membrane, and step S22 includes: S221, mixing a solid electrolyte precursor with a binder to obtain a second mixture; S222, rolling the second mixture to obtain a solid electrolyte green film; S223, sintering the solid electrolyte green film to obtain a solid electrolyte membrane.

[0069] The density of the solid electrolyte green film will affect the density of the subsequently obtained solid electrolyte membrane. By mixing the solid electrolyte precursor with the binder and then rolling it, a solid electrolyte green film with a preliminary shape and good density can be obtained. After sintering, the solid electrolyte green film is transformed into a solid electrolyte membrane with a fixed shape, and the density of the solid electrolyte membrane with a fixed shape is improved.

[0070] In some embodiments, the content of the solid electrolyte precursor in the second mixture is 90wt%~99wt%, and the content of the binder is 1wt%~10wt%. By controlling the content of the binder to ensure that the solid electrolyte raw film can be effectively formed, the content of the solid electrolyte precursor is increased as much as possible, which is conducive to improving the compactness of the solid electrolyte membrane. As an example, in the second mixture, the content of the solid electrolyte precursor is 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%, and the content of the binder is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0071] In some embodiments, the binder includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyacrylic acid (PAA) and carboxymethyl cellulose (CMC). The above-mentioned binder is an organic high molecular polymer, which can provide cohesive force for the solid electrolyte precursor during the rolling process, so that the particles in the solid electrolyte precursor are combined together and formed into a solid electrolyte green film through extrusion, and during the sintering process, these organic substances will be thermally decomposed under the action of high temperature, so that the obtained solid electrolyte membrane mainly contains oxide solid electrolyte, thereby improving the ionic conductivity of the solid electrolyte.

[0072] In some embodiments, the roller pressing process is a hot pressing process, and the hot pressing temperature is 50°C to 120°C. Usually, the binder is an organic high molecular polymer. Controlling the hot pressing temperature during the hot pressing process can make the binder deform appropriately but the binder is not easy to decompose at high temperature, which can promote the densification of the solid electrolyte film and thus improve the density of the solid electrolyte film. As an example, the hot pressing temperature is 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.

[0073] In some embodiments, the rolling pressure of the rolling process is 120MPa to 180MPa. Within this rolling range, the density of the obtained solid electrolyte green film can be better, thereby improving the density of the solid electrolyte film. As an example, the rolling pressure is 120MPa, 130MPa, 140MPa, 150MPa, 160MPa, 170MPa or 180MPa.

[0074] In some embodiments, the thickness of the solid electrolyte green film is 100 μm to 300 μm. The thickness of the solid electrolyte film is positively correlated with the solid electrolyte green film. If the solid electrolyte green film is thick, the obtained solid electrolyte film is thick, and if the solid electrolyte green film is thin, the obtained solid electrolyte film is thin. As an example, the thickness of the solid electrolyte green film is 100 μm, 120 μm, 140 μm, 150 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm or 300 μm.

[0075] In some embodiments, the sintering temperature of the sintering process is 1000°C to 1300°C, and the sintering time is 5min to 10h. As an example, the sintering temperature is 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C or 1300°C; the sintering time is 5min, 10min, 30min, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h. The sintering temperature is related to the chemical composition of the oxide solid electrolyte. As an example, for LLZO, LLZTO, LLAZO and LLGZO, the sintering temperature can be set to 1050°C to 1200°C; for LLTO, the sintering temperature can be set to 1100°C to 1200°C.

[0076] In some embodiments, the sintering process includes increasing the temperature from room temperature to a sintering temperature at a first heating rate, sintering at the sintering temperature for a sintering time, and decreasing the temperature from the sintering temperature to room temperature at a first cooling rate.

[0077] In some embodiments, the first heating rate is (8-12) C° / min. As an example, the first heating rate is 8 C° / min, 9 C° / min, 10 C° / min, 11 C° / min or 12 C° / min.

[0078] In some embodiments, the first cooling rate is (4-6) C° / min. As an example, the first cooling rate is 4 C° / min, 4.5 C° / min, 5 C° / min, 5.5 C° / min or 6 C° / min.

[0079] In a fifth aspect, an embodiment of the present application further provides a battery, comprising the solid electrolyte as described above or a solid electrolyte prepared by the solid electrolyte preparation method as described above.

[0080] In some embodiments, the battery includes at least one of a solid-state battery and a liquid-state battery. The solid-state battery includes at least one of an all-solid-state battery and a package solid-state battery.

[0081] Example 1 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:1 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0082] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0083] Example 2 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:0.5 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0084] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0085] Example 3 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:2 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0086] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0087] Example 4 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:3 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0088] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0089] Example 5 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:4 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0090] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0091] Example 6 S1. Lithium source coating: LLZO and LiOH were mixed in a Li element molar ratio of 10:5 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain LiOH-coated LLZO powder.

[0092] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0093] Example 7 S1. Lithium source coating: LLZO and Li2CO3 were mixed in a Li element molar ratio of 10:1 and added into water; the mixture was evenly dispersed by ball milling at 500 rpm for 12 h; after the ball milling, the mixture was dried to obtain Li2CO3-coated LLZO powder.

[0094] S2. Preparation of electrolyte membrane: LLZO powder is pressed into tablets at a pressure of 150 MPa to prepare an electrolyte green membrane with a diameter of 16 mm and a thickness of 200 um; the electrolyte green membrane is placed in a magnesium oxide crucible and placed in a muffle furnace for high-temperature sintering. The heat treatment conditions are: heating rate 10 C° / min; holding temperature 1200 C°, holding time 3 h, cooling rate 5 C° / min, to obtain a ceramic electrolyte membrane (i.e., solid electrolyte membrane).

[0095] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the solvent is replaced with isopropanol in which LiOH is poorly soluble, and the remaining steps and conditions are exactly the same.

[0096] The ceramic electrolyte membranes prepared in the examples and comparative examples were tested as follows: 1. The powders prepared in step S1 of Example 1 and Comparative Example 1 were photographed using a scanning electron microscope. Figure 2 The scanning electron microscope image of the LiOH-coated LLZO powder of Example 1 of the present application is shown. Figure 2 It can be seen that in the LiOH-coated LLZO powder prepared in Example 1, the lithium source LiOH is more evenly coated on the surface of the spherical LLZO powder; Figure 3 The figure shows a scanning electron microscope image of a powder obtained by mixing LiOH and LLZO in Comparative Example 1 of the present application, i.e., a conventional lithium-supplemented oxide solid electrolyte powder. Figure 3 It can be seen that the lithium source particles in the powder prepared in Comparative Example 1 are unevenly distributed.

[0097] 2. The ceramic electrolyte membranes prepared in Example 1 and Comparative Example 1 were photographed using a scanning electron microscope. Figure 4 The scanning electron microscope image of the ceramic electrolyte membrane of Example 1 of the present application is shown. Figure 4It can be seen that the ceramic electrolyte membrane prepared in Example 1 has uniform and dense grain growth without obvious defects; Figure 5 The SEM image of the ceramic electrolyte powder of Comparative Example 1 of the present application is shown. Figure 5 It can be seen that there are obvious point defects in the ceramic electrolyte membrane prepared in Comparative Example 1, and these defects can easily cause the electrolyte membrane to fail.

[0098] 3. Test the critical current density of the ceramic electrolyte membrane provided in Examples 1 to 7 and Comparative Example 1: Two lithium foils were laminated with the solid electrolyte membrane, and close interface contact between the solid electrolyte membrane and the lithium foil was achieved by isostatic pressing. The isostatic pressing condition was maintained at 250 MPa for 10 min. Button batteries were used for packaging, and then the charge and discharge tests were performed using an electrochemical workstation MetrohmAutolab. The current density was 0.1 mA / cm 2 Increase in sequence, each increase is 0.1mA / cm 2 Until the symmetrical battery short circuit occurs. The test results are recorded in Table 1.

[0099] Table 1

[0100] Compared with Comparative Example 1, Example 1 has the same parameters except for the different solvents. It can be seen from the results of the two in Table 1 that, compared with Comparative Example 1, the critical current density of the ceramic electrolyte membrane provided in Example 1 is about three times that of the ceramic electrolyte membrane provided in Comparative Example 1, and the critical current density is significantly improved, which indicates that the performance of the ceramic electrolyte membrane provided in Example 1 in transporting ions is better than that of the ceramic electrolyte membrane provided in Comparative Example 1. This is because, in Example 1, LiOH can be dissolved in water, so that after mixing, ball milling and drying, LiOH can be evenly coated on the surface of LLZO powder, thereby ensuring the uniformity of lithium supplementation during high-temperature sintering, and then improving the critical current density of the obtained ceramic electrolyte membrane. In Comparative Example 1, LiOH is difficult to dissolve in isopropanol, so that LiOH is difficult to evenly coat on the surface of LLZO powder, which will lead to uneven lithium supplementation during high-temperature sintering, and the critical current density of the ceramic electrolyte membrane is difficult to improve.

[0101] Compared with Example 2, Example 1, and Example 3 to Example 6, the molar ratio of the Li element of LLZO and LiOH gradually decreases, that is, the amount of LiOH added increases. From the results in Table 1, it can be seen that as the amount of LiOH added increases, the critical current density of the ceramic electrolyte membrane first increases and then decreases. This is because as the amount of LiOH added increases, the amount of lithium supplementation increases, the quality of LLZO in the ceramic electrolyte membrane is improved, and thus the critical current density increases; in the case of a small amount of excess LiOH, lithium can remain at the grain boundary to form a lithium-rich phase, thereby making the LLZO grains better connected and improving the density of the ceramic electrolyte membrane obtained after sintering; however, too much LiOH will affect the uniformity of LLZO in the ceramic electrolyte membrane, resulting in a decrease in the critical current density of the ceramic electrolyte membrane.

[0102] The only difference between Example 1 and Example 7 is that different lithium supplement agents are used. From the results in Table 1, it can be seen that the critical current densities of the ceramic electrolyte membranes prepared using Li2CO3 and LiOH as lithium supplement agents are similar. This is because Li2CO3 and LiOH have similar properties, can provide lithium ions and can be dissolved in water, so they can be evenly coated on the surface of LLZO powder, thereby effectively improving the uniformity of LLZO in the sintered ceramic electrolyte membrane.

[0103] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0104] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0105] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.

[0106] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A solid electrolyte precursor, characterized in that: The solid electrolyte precursor is a core-shell structure, including a core composed of an oxide solid electrolyte and a shell composed of a lithium supplement.

2. The solid electrolyte precursor according to claim 1, characterized in that The ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:(0.5~5).

3. The solid electrolyte precursor according to claim 1, characterized in that The lithium supplement includes at least one of lithium hydroxide, lithium carbonate and lithium oxide.

4. The solid electrolyte precursor according to claim 1, characterized in that The oxide solid electrolyte is in the form of spherical or quasi-spherical particles.

5. The solid electrolyte precursor according to claim 1, characterized in that The average particle size of the oxide solid electrolyte is 5 nm to 1 μm.

6. A method for preparing a solid electrolyte precursor, characterized in that: include: Adding a lithium supplement agent and an oxide solid electrolyte into a solvent for mixing to obtain a first mixture, wherein the lithium supplement agent is dissolved in the solvent; The first mixture is dried to remove the solvent so that the lithium supplement agent is precipitated and forms a coating layer covering the surface of the oxide solid electrolyte, thereby obtaining a solid electrolyte precursor with a core-shell structure.

7. The method for preparing a solid electrolyte precursor according to claim 6, characterized in that: The lithium supplement includes an inorganic lithium compound, and the solvent includes water.

8. The method for preparing a solid electrolyte precursor according to claim 7, characterized in that: The inorganic lithium compound includes at least one of lithium hydroxide, lithium carbonate and lithium oxide.

9. The method for preparing a solid electrolyte precursor according to claim 6, characterized in that: The oxide solid electrolyte comprises at least one of lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium aluminum oxide, lithium lanthanum zirconium gallium oxide, lithium lanthanum titanium oxide, lithium aluminum germanium phosphate and lithium aluminum titanium phosphate; and / or, In the first mixture, the ratio of the amount of lithium in the oxide solid electrolyte to the amount of lithium in the lithium supplement is 10:(0.5-5); and / or, In the first mixture, the average particle size of the oxide solid electrolyte is 5 nm to 1 μm.

10. The method for preparing a solid electrolyte precursor according to any one of claims 6 to 9, characterized in that: The method for preparing the solid electrolyte precursor further includes: before preparing the first mixture, performing a sand grinding process on the oxide solid electrolyte so that the oxide solid electrolyte is in the form of spherical or quasi-spherical particles.

11. The method for preparing a solid electrolyte precursor according to any one of claims 6 to 9, characterized in that: The method for preparing the solid electrolyte precursor further includes: before drying the first mixture, ball milling the first mixture.

12. The method for preparing a solid electrolyte precursor according to any one of claims 6 to 9, characterized in that: The preparation process of the first mixture comprises: Adding a lithium supplement agent into a solvent for dissolution to obtain a first solution; An oxide solid electrolyte is added into the first solution and stirred to obtain a first mixture.

13. A solid electrolyte, characterized in that: The solid electrolyte is obtained by sintering a solid electrolyte precursor prepared by the solid electrolyte precursor according to any one of claims 1 to 5 or the solid electrolyte precursor prepared by the preparation method of any one of claims 6 to 12.

14. A method for preparing a solid electrolyte, characterized in that: include: Providing a solid electrolyte precursor, wherein the solid electrolyte precursor is a solid electrolyte precursor according to any one of claims 1 to 5 or a solid electrolyte precursor prepared by the preparation method of a solid electrolyte precursor according to any one of claims 6 to 12; The solid electrolyte precursor is sintered to obtain a solid electrolyte.

15. The method for preparing a solid electrolyte according to claim 14, characterized in that: The solid electrolyte is a solid electrolyte membrane, and the solid electrolyte precursor is sintered to obtain the solid electrolyte, comprising: mixing the solid electrolyte precursor with a binder to obtain a second mixture; Roll-pressing the second mixture to obtain a solid electrolyte green film; The solid electrolyte green film is sintered to obtain a solid electrolyte membrane.

16. The method for preparing a solid electrolyte according to claim 15, characterized in that: The sintering temperature of the sintering treatment is 1000° C. to 1300° C., and the sintering time is 5 min to 10 h.

17. A battery, characterized in that: A solid electrolyte comprising the solid electrolyte as claimed in claim 13 or a solid electrolyte prepared by the method for preparing a solid electrolyte as claimed in any one of claims 14 to 16.

Citation Information

Patent Citations

  • Lithium-lanthanum-zirconium oxide-based solid electrolyte material capable of inhibiting lithium dendrites, and preparation method and application thereof

    CN110176627A

  • Positive electrode material for solid-state battery as well as preparation method and application of positive electrode material

    CN115036509A

  • Modified lithium manganate positive electrode material and preparation method thereof

    CN116632189A

  • Carbon-coated lithium iron phosphate, preparation method thereof and lithium battery

    CN119297254A

Cited By

  • Solid-state electrolyte precursor, preparation method of solid-state electrolyte, solid-state electrolyte and solid-state battery

    CN120413836A